Recessive aminoacyl-tRNA synthetase disorders: lessons learned from in vivo disease models - Kalotay, Elizabeth; Klugmann, Matthias; Housley, Gary D.; Fröhlich, Dominik (Frontiers in Neuroscience, 2023)
Protein synthesis is a fundamental process that underpins almost every aspect of cellular functioning. Intriguingly, despite their common function, recessive mutations in aminoacyl-tRNA synthetases (ARSs), the family of enzymes that pair tRNA molecules with amino acids prior to translation on the ribosome, cause a diverse range of multi-system disorders that affect specific groups of tissues. Neurological development is impaired in most ARS-associated disorders. In addition to central nervous system defects, diseases caused by recessive mutations in cytosolic ARSs commonly affect the liver and lungs. Patients with biallelic mutations in mitochondrial ARSs often present with encephalopathies, with variable involvement of peripheral systems. Many of these disorders cause severe disability, and as understanding of their pathogenesis is currently limited, there are no effective treatments available. To address this, accurate in vivo models for most of the recessive ARS diseases are urgently needed. Here, we discuss approaches that have been taken to model recessive ARS diseases in vivo, highlighting some of the challenges that have arisen in this process, as well as key results obtained from these models. Further development and refinement of animal models is essential to facilitate a better understanding of the pathophysiology underlying recessive ARS diseases, and ultimately to enable development and testing of effective therapies.